2003
DOI: 10.1016/s0266-7681(03)00011-1
|View full text |Cite
|
Sign up to set email alerts
|

Palmar Plate Fixation of AO Type C2 Fracture of Distal Radius Using a Locking Compression Plate –A Biomechanical Study in a Cadaveric Model

Abstract: The stability of palmar plate fixation using a locking compression T-plate was compared with that of a conventional palmar T-plate and a dorsal T-plate in a cadaveric model of an AO type C2 fracture of distal radius. The wrist axial load transmission through the radius was tested for each fixation. The results show that, under 100N axial load, the palmar locking compression T-plate restores stability comparable to that of the intact radius, and is superior to conventional palmar or dorsal T-plates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
0
19

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(111 citation statements)
references
References 16 publications
3
89
0
19
Order By: Relevance
“…However, the results of this study can be supported by biomechanical research, which demonstrated that the VLP device was efficient in the restoration of the normal axial force alignment without the reliance on screw engagement into the bone due to the nature of the screws, which mediate better locking mechanism into osteoporotic bone. 31 Additionally, the data proves coherent with Jupiter et al who studied ≥60 years patients and concluded that open reduction VLPs could be used to treat displaced distal radial fractures in older patients when conservative managements have failed, although our data considers the technique as primary management. 32 We cannot fully explain why older patients had better ulna deviation, but we hypothesise that it may be due to ulna shortening after fracture, which more commonly occurs in osteoporotic bone.…”
Section: Discussionsupporting
confidence: 86%
“…However, the results of this study can be supported by biomechanical research, which demonstrated that the VLP device was efficient in the restoration of the normal axial force alignment without the reliance on screw engagement into the bone due to the nature of the screws, which mediate better locking mechanism into osteoporotic bone. 31 Additionally, the data proves coherent with Jupiter et al who studied ≥60 years patients and concluded that open reduction VLPs could be used to treat displaced distal radial fractures in older patients when conservative managements have failed, although our data considers the technique as primary management. 32 We cannot fully explain why older patients had better ulna deviation, but we hypothesise that it may be due to ulna shortening after fracture, which more commonly occurs in osteoporotic bone.…”
Section: Discussionsupporting
confidence: 86%
“…29 They reported that if the volarily placed titanium symmetry plate was used to fix a colles -type fracture, the distal fragment of radius to develop a dorsal angulations of about 9 degrees if early active mobilization of fingers was initiated during the postoperative period, on the other hand, Leung et al demonstrated no statistical difference between axial loading transmission though the intact radius and a distal radius fracture fix with a volar locking plate. 30 In fact, the volar locking plate showed advantages over dorsal plating in the fixation of dorsally unstable distal radius fracture. In addition, volar plate fixation is a valuable method because of decrease risk of inducing dorsal soft tissue complications.…”
Section: Discussionmentioning
confidence: 99%
“…그러나 비수술적 치료 후 관절내 골편의 해부학적 정복의 실패와 연관된 불안정성, 손목 관절의 운 동 장애, 근력 약화, 동통, 부종, 퇴행성 관절염 등의 문제 가 보고되었다 6,19) . 이러한 원위 요골 골절의 합병증을 감 소시키고 해부학적 정복을 목적으로 여러 가지의 수술적 방법이 소개되어 왔다 16) . …”
Section: 결 과unclassified